Physiology and development of grafted dwarf cashew seedlings under different fertilization doses and irrigated with saline water - thamiris; Alves Bezerra, Marlos; Morais Lima, Reivany Eduardo; de Oliveira Feitosa, Hernandes; Gomes Dias, Gabrielen de Maria (Comunicata Scientiae, 2024)
Salinity is one of the primary challenges faced by irrigated agriculture in semi-arid regions. This study aimed to investigate the effects of fertilization on the development of cashew seedlings irrigated with water of varying salinity levels. The research was conducted in a protected environment at Embrapa Agroindústria Tropical, Fortaleza, using grafted seedlings of the BRS 189 clone on CCP 06 rootstock. The treatments resulted from the combination of three levels of NPK fertilization (control - without fertilization, 50% less than conventional nutrition, and 100% of conventional nutrition used by the crop), which was incorporated into the substrate before sowing CCP 06, with four salinity levels (ECa of 0.8, 4.0, 7.0, and 10.0 dS m-1) of the irrigation water for the seedlings. Gas exchange, assimilate accumulation, growth, and nutrient content in the leaves, stems, and roots of the seedlings were evaluated 90 days after grafting. The data were subjected to analysis of variance, and when a significant effect was observed, the Tukey test was performed, while quantitative data were subjected to regression analysis. Overall, fertilization levels did not influence seedling growth. Fertilization did not interfere with photosynthate production, which performed better when the seedlings were subjected to a salinity of 7.0 dS m-1. The application of NPK to the substrate resulted in higher levels of nitrogen in the leaves, while phosphorus content decreased, and foliar potassium was not influenced by fertilization.